Pembuatan, Uji Fungsi, Dan Uji Durabilitas Alat Pengambilan Sampel Udara Portabel - Saputra, Arie Ikhwan; Mely Gustina; Aplina Kartika Sari; Suksmerri; Darwel (Jurnal Sanitasi Profesional Indonesia, 2025)
This study aims to develop, test the function, and evaluate the durability of a portable air sampling device based on an impinger system as a low-cost alternative to commercial air samplers, which are currently expensive and difficult to access for regional institutions. The device was designed using easily purchased components, including a lithium-ion battery, vacuum pump, rotameter, and an SNI-standard impinger tube. The tool was assembled in a workshop and tested for functionality, sampling stability, and battery endurance. A comparative test was conducted with a standard air sampler owned by Poltekkes Kemenkes Padang. The prototype demonstrated stable airflow at 0.5 L/min for up to 4 hours, outperforming some commercial tools in portability due to its integrated battery and solar-charging capability. Comparative sampling for SO₂, CO, and NO₂ showed no significant difference between the prototype and standard devices. The device is also significantly cheaper, costing under 7 million IDR compared to commercial units priced at 47–94 million IDR. This study concludes that the prototype is feasible for field sampling and suitable as an affordable alternative for air quality monitoring.